The Effect of Digital Technology Adoption On Industry 4.0 Readiness and Business Performance of Culinary MSMEs in Bogor Regency - Alifudin, Meygy; Mulyati, Heti; Mahfudz, Naufal (Jurnal Manajemen dan Organisasi, 2024)
MSMEs significantly contribute to employment and economic growth, particularly in Indonesia, and impact the socioeconomic conditions of the lower middle-class community. The Fourth Industrial Revolution has transformed the fundamental managerial aspects of the industry. The aim of this era was to revolutionise industries through digitalisation. Digital technology can help MSMEs adapt swiftly and accelerate through digital transformation. This study investigates the influence of digital technology on the preparedness of MSMEs in Bogor Regency, West Java Province, for Industry 4.0, and on enhancing business performance using the Technology Acceptance Model (TAM). This study employs a quantitative approach with structural equation modelling (SEM) analysis tools for 116 business actors. Readiness indicators are measured using organizational resilience, infrastructure systems, manufacturing systems, data transformation, and digital technology. The findings of this study indicate that the adoption of digital technology by business actors has a minimal and insignificant impact on business performance in MSMEs, but does influence the preparedness of MSMEs to face Industry 4.0. Readiness indicators indirectly affect the use of digital technology and business performance.